Board meeting frequency and firm performance - Vafeas, Nikos (Journal of Financial Economics, 1999)
For 307 firms over the 1990–1994 period, I find that board meeting frequency is related to corporate governance and ownership characteristics in a manner that is consistent with contracting and agency theory. The annual number of board meetings is inversely related to firm value. This result is driven by increases in board activity following share price declines. I further find that operating performance improves following years of abnormal board activity. These improvements are most pronounced for firms with poor prior performance and firms not engaged in corporate control transactions. Overall, my results suggest that board activity, measured by board meeting frequency, is an important dimension of board operations.